Impact of dried seaweed meal on heat-stressed lactating dairy cattle - B. Cvetkovic; John E. Shirley; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2004)
Twenty-four lactating Holstein cows were used to determine the production response to the inclusion of brown seaweed in the basal diet during summer heat stress. Cows were blocked by lactation number, days in milk, and energy-corrected milk and then allotted to either a control or control + brown seaweed diet. Cattle on the brown seaweed diet were fed 4 ounces per cow per day for 7 days , and then 2 ounces per cow per day for 14 days, before the start of the experiment. All cattle were housed in a tie-stall barn, fed individually, and milked twice daily. Cows fed brown seaweed produced more (P<0.01) milk (77.6 vs 73.8 lb) and milk protein than controls did. But the addition of brown seaweed did not reduce respiration rates, rectal temperature, or rear-udder skin temperature. This indicated a similar heat-stress response for treated and control cows. Other studies have shown a reduction in respiration rates and body temperature when stressed cattle were fed brown seaweed. Further investigation is necessary to determine the factors that resulted in the observed milk and milk-protein responses in this study.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Heat stress; Nutrition; Milk production